Pinkment: a synthetic platform for the development of fluorescent probes for diagnostic and theranostic applications. Issue 32 (6th August 2020) - Weber, Maria; Han, Hai-Hao; Li, Bo-Han; Odyniec, Maria L.; Jarman, Charlotte E. F.; Zang, Yi; Bull, Steven D.; Mackenzie, Amanda B.; Sedgwick, Adam C.; Li, Jia; He, Xiao-Peng; James, Tony D.
Abstract : Pinkment, a resorufin based ONOO − selective and sensitive 'plug and play' fluorescence-based platform for in vitro and in vivo use, enables facile functionalisation for various imaging and theranostic applications. Abstract : Reaction-based fluorescent-probes have proven successful for the visualisation of biological species in various cellular processes. Unfortunately, in order to tailor the design of a fluorescent probe to a specific application ( i.e. organelle targeting, material and theranostic applications) often requires extensive synthetic efforts and the synthetic screening of a range of fluorophores to match the required synthetic needs. In this work, we have identified Pinkment-OH as a unique "plug-and-play" synthetic platform that can be used to develop a range of ONOO − responsive fluorescent probes for a variety of applications. These include theranostic-based applications and potential material-based/bioconjugation applications. The as prepared probes displayed an excellent sensitivity and selectivity for ONOO − over other ROS. In vitro studies using HeLa cells and RAW 264.7 macrophages demonstrated their ability to detect exogenously and endogenously produced ONOO − . Evaluation in an LPS-induced inflammation mouse model illustrated the ability to monitor ONOO − production in acute inflammation. Lastly, theranostic-based probes enabled the simultaneous evaluation of indomethacin-based therapeutic effects combined with the visualisation of an inflammation biomarker in RAW 264.7 cells.